Atlas of mildly and highly insoluble matrisome driving liver fibrosis - Zhang, Wen; Zhang, Ning; Wu, Wenyue; Li, Hong; You, Hong; Chen, Wei (Frontiers in Pharmacology, 2024)
The excessive deposition and cross-linking of core matrisome components typically result in abnormal remodeling of the extracellular matrix (ECM), leading to increased liver stiffness and worsening liver fibrosis. Exploring the biochemical properties of the ECM scaffold can deepen our understanding of the pathological mechanisms driving liver fibrosis and potentially facilitate the identification of therapeutic targets. While traditional sodium dodecyl sulfate (SDS)-based liver decellularization followed by proteomics can uncover the matrisome components within the ECM scaffold, it lacks the ability to reveal physicochemical characteristics like solubility. In our present study, using adult mouse liver as an example, we introduced a novel two-step workflow that combines our previously enhanced SDS (ESDS) decellularization with the conventional SDS method, enabling the identification of matrisome members with mild and/or high solubilities. Through this approach, we visualized the atlas of the mildly and highly insoluble matrisome contents in the adult mouse liver, as well as the regulatory network of highly insoluble matrisome that largely governs liver stiffness. Given the strong correlation between increased matrisome insolubility and heightened ECM stiffness, we believe that this methodology holds promise for future research focused on liver stiffness.